Life cycle impacts of forest management and wood utilization on carbon mitigation: knowns and unknowns. Issue 3 (June 2011) - Lippke, Bruce; Oneil, Elaine; Harrison, Rob; Skog, Kenneth; Gustavsson, Leif; Sathre, Roger
This review on research on life cycle carbon accounting examines the complexities in accounting for carbon emissions given the many different ways that wood is used. Recent objectives to increase the use of renewable fuels have raised policy questions, with respect to the sustainability of managing our forests as well as the impacts of how best to use wood from our forests. There has been general support for the benefits of sustainably managing forests for carbon mitigation as expressed by the Intergovernmental Panel on Climate Change in 2007. However, there are many integrated carbon pools involved, which have led to conflicting implications for best practices and policy. In particular, sustainable management of forests for products produces substantially different impacts than a focus on a single stand or on specific carbon pools with each contributing to different policy implications. In this article, we review many recent research findings on carbon impacts across all stages of processing from cradle-to-grave, based on life cycle accounting, which is necessary to understand the carbon interactions across many different carbon pools. The focus is on where findings are robust and where uncertainties may be large enough to question key assumptions that impact carbon in the forest and its many uses. Many opportunities for reducing carbon emissions are identified along with unintended consequences of proposed policies.